Presus Tic Facialis Sinistra Pada Riwayat Operasi Benjolan - Setyo Puji Nugroho Sakti (Jurnal Kesehatan dan Fisioterapi, 2022)
Abstract-Facial tic is a symptom of involuntary facial muscles caused by involuntary movements as a result of various activities such as stress, or genetic disorders. The presence of surgical scars also causes lumps on the face and eyes as proposed in this study, namely hemifacial spasm. The patient named Mr. Joko Purwanto in November 2021 underwent eye surgery because of a lump in his left eye, after the operation he complained of twitching; can't open his eyes wide. From the neurologist to the eye, he was referred to physiotherapy. Physiotherapy is usually done once a week every Saturday. Implementation is done with IR Luminious. After doing physiotherapy, the patient with complaints when he first came was difficulty moving the left side of the face, a feeling of twitching on the left side of the face. After receiving physiotherapy treatment for 2 times, starting from January 15, 2022 to January 18, 2022, it showed good changes. Now the feeling of twitching on the left side of the face has reduced, the face looks symmetricalKeywords: tic facialis, physiotherapy, lump